1999
DOI: 10.1523/jneurosci.19-14-05919.1999
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Brain-Derived Neurotrophic Factor Enhances Sensory Innervation and Selectively Increases Neuron Number

Abstract: Target-derived neurotrophin growth factors have significant effects on the development and maintenance of the mammalian somatosensory system. Studies of transgenic mice that overexpress neurotrophins NGF and neurotrophin 3 (NT-3) at high levels in skin have shown increased sensory neuron number and enhanced innervation of specific sensory ending types. The effects of two other members of this family, BDNF and NT-4, on sensory neuron development are less clear. This study examined the role of brain-derived neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 61 publications
4
89
0
Order By: Relevance
“…Experimental animals consisted of C57BL/6J wild-type mice (The Jackson Laboratory, Bar Harbor, ME) and transgenic mice that overexpress BDNF under the control of a cytokeratin-14 promoter/enhancer (BDNF-OE) (LeMaster et al, 1999) aged 6 -16 weeks. The transgenic mice have enhanced expression of BDNF in cells that express keratin 14 (K-14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental animals consisted of C57BL/6J wild-type mice (The Jackson Laboratory, Bar Harbor, ME) and transgenic mice that overexpress BDNF under the control of a cytokeratin-14 promoter/enhancer (BDNF-OE) (LeMaster et al, 1999) aged 6 -16 weeks. The transgenic mice have enhanced expression of BDNF in cells that express keratin 14 (K-14).…”
Section: Methodsmentioning
confidence: 99%
“…The neurotrophin family of neuronal growth factors (e.g., NT4, BDNF, NGF), or their molecular receptors, have been shown in nongustatory sensory systems to influence peripheral innervation, for example, innervation of the inner ear by eighth nerve ganglion cells (Schimmang et al, 1995), and innervation of cutaneous receptors by dorsal root ganglion cells (Fundin et al, 1997;LeMaster et al, 1999). Neurotrophins also influence the central growth of connections from peripheral sensory receptors to the brain (Buckland and Cunningham, 1998;Caminos et al, 1999;Patel et al, 2003).…”
Section: Neurotrophins and Innervation Densitymentioning
confidence: 99%
“…Therefore, this technique generates reliable estimates of cell number in the nervous system (Coggeshall, 1992;Clarke, 1993). An estimate of the number of proprioceptive cells in each LDRG (L3-L4) and TDRG (T4 -T6) was obtained by multiplying the average number of profiles per section by the length of the DRG (Davis et al, 1996;LeMaster et al, 1999).…”
Section: Cell Countingmentioning
confidence: 99%
“…Fourth, even the developing sensory neurons that normally survive die if deprived of an essential trophic factor during the cell death period. For many sensory neurons including those expressing substance-P the trophic factor is NGF, but some classes of sensory neurons depend on other members of the NGF family (called ÔneurotrophinsÕ), notably BDNF and NT-3 [15][16][17][18][19][20], or members of other protein families [21]. Fifth, NGF-dependent sensory neurons obtain their NGF exclusively from their target territory, where it is synthesized, and remove it by retrograde transport in sufficiently large quantities to greatly deplete its concentration in the target [22,23].…”
Section: Interaxonal Competition As a Determinant Of Neuronal Death Imentioning
confidence: 99%
“…Sixth, raising the concentration of NGF (or other neurotrophins) in the axonal target region above normal levels reduces neuronal death, causing ganglionic hypertrophy [6,7]. Most such experiments involved the systemic administration of exogenous trophic factor, but Albers et al [25,26] showed that transgenic mice overexpressing NGF in the epidermis (but not elsewhere) were subject to greatly reduced death of sensory ganglion neurons, and a similar approach has subsequently been used to show reduced ganglion neuron death following cutaneous overexpression of NT-3 [19] or BDNF [18].…”
Section: Interaxonal Competition As a Determinant Of Neuronal Death Imentioning
confidence: 99%